1990
DOI: 10.1128/jb.172.2.1043-1050.1990
|View full text |Cite
|
Sign up to set email alerts
|

Induction of levansucrase in Bacillus subtilis: an antitermination mechanism negatively controlled by the phosphotransferase system

Abstract: The target of the induction by sucrose of the levansucrase gene is a transcription terminator (sacRt) located upstream from the coding sequence, sacB. The two-gene locus sacX-sacY (formerly sacS) and the ptsI gene were previously shown to be involved in this induction. ptsI encodes enzyme I of the phosphoenolpyruvate-dependent phosphotransferase system. SacX is strongly homologous to sucrose-specific phosphotransferase system-dependent permeases. SacY is a positive regulator of sacB. Here we show that SacY is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 36 publications
(40 reference statements)
9
149
0
Order By: Relevance
“…4). These transcripts were of the expected lengths (about 2200, 2400, 1100 and 1650 nt, for amyE, sacC, csn and sacB, respectively), in agreement with the previously determined site of transcription initiation in the sacR leader sequence (Shimotsu & Henner, 1986) and generated by transcriptional antitermination at the terminator structure present in sacR (Crutz et al, 1990). A short additional transcript which hybridized only with the 5h sacR probe was observed in the case of sacC (Fig.…”
Section: Resultssupporting
confidence: 89%
“…4). These transcripts were of the expected lengths (about 2200, 2400, 1100 and 1650 nt, for amyE, sacC, csn and sacB, respectively), in agreement with the previously determined site of transcription initiation in the sacR leader sequence (Shimotsu & Henner, 1986) and generated by transcriptional antitermination at the terminator structure present in sacR (Crutz et al, 1990). A short additional transcript which hybridized only with the 5h sacR probe was observed in the case of sacC (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The bglR-encoded protein is homologous to regulatory proteins of the BglG family. All previously described members of this family control the utilization of sugars (1,13,15,16,36,39,40). Disruption of bglR revealed that its product is required for maximal growth on arbutin and salicin as sole carbon sources.…”
Section: Methodsmentioning
confidence: 99%
“…These systems include the control of the Bacillus subtilis levansucrase sacB gene by SacY (7,13), of the B. subtilis sacPA operon by SacT (6,14,39), of B. subtilis 13-glucan utilization by licT (40), of Lactobacillus casei lactose utilization (1), and of the Erwinia chrysanthemi P-glucoside phosphotransferase gene arbF by ArbG (15).…”
mentioning
confidence: 99%
“…These proteins (SacY, SacT, LicT, and GlcT) positively control the genes involved in the metabolism of carbohydrates that are taken up by the PTS; SacY and T are involved in sucrose metabolism, LicT in the metabolism of oligo--glucoside and aryl--glucoside, and GlcT in glucose assimilation. SacY and T [140][141][142] are antiterminators of the sacB (encoding levansucrase)-levB (endolevanase)-yveA, sacX (IIBC SacX )-sacY, and sacP (IIBC SacP )-sacA (sucrose-6-P hydrolase)-ywdA operons, whereas LicT 27,143) is an antiterminator of the licS gene (endo-1,3-1,4--glucanase) and the bglP (IIBCA Bgl )-bglH (6-P--glucosidase)-yxiE operon, and GlcT 144,145) is that of the ptsG (IICBA Glc )-ptsH (HPr)-ptsI (EI) operon. In the presence of the cognate PTS-sugars that activate these antiterminators, they bind to a conserved motif called the ribonucleic antiterminator (RAT), which is present in the untranslated leader-mRNAs of their target genes.…”
Section: Catabolite Control Mediated By Ccpb Ccpc Ccpn and Cggrmentioning
confidence: 99%